Ethno-botanical survey of Palamalai Hills, Mettur Taluk, Eastern Ghats, India - E. G. Wesely, L. Thamaraiselvi; Bobby, M.D. Nazneen; Nathan, Vinod Kumar (Current Botany, 2018)
Ethnobotanical survey of Palamali hills, a part of Eastern Ghats was carried out for reporting the preliminary traditional knowledge from the inhabitant tribal community. Through the survey, we identified 18 plants which possess medicinal properties. This report is a preliminary checklist and will be helpful for people in identifying potential bioresource and initiating conservatory measures. The present investigation showed that, the tribes of Palamalai Hills of Mettur Taluk, Eastern Ghats, India possess rich knowledge of the medicinal plants and their utilization. There is a need of scientific awareness for prevention of most of the diseases and the cultivation of above medicinal plants for both the utilization and the conservation of natural resources.